UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MELALUI VARIASI PEMBELAJARAN PESERTA DIDIK - Budiantoro, Paino; Haetami, Mimi; Haetami, Mimi; Hidasari, Fitriana Puspa; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The problem in this research is how to improve learning outcomes passing under volleyball through variation of learning in class VII students SMP Negeri 1 MeliauSanggau District Academic Year 2016/2017 ?. The purpose of this study is to improve the effectiveness in the learning process passing under the volley through variations of learning.This study uses classroom action research which is the basis for improving the learning that will be produced, with the following steps: 1) Planning; 2) implementation; 3) observation; 4) reflection; Subjects in use as many as 40 students. Data were collected by questionnaire / questionnaire and test each cycle. From the results of the research In the preliminary test before the action was seen that the value of learning passing below the average volleyball class 50.05 and the number of percentage of classical completeness only reached 30%. In the first cycle action with learning method using learning variation on learning passing under volleyball obtained grade average grade 68,3 percentage of classical completeness 62,5%. In the second cycle action with learning method using learning variation on learning passing under volleyball obtained grade average value that is 81,05 the percentage of classical completeness also increase until reach 85% and observation value of student activity is better.Â Keywords : Learning, Passing Down, Volleyball, Variations.